Perioperative Management Patients with Meningioma C1-2 - Bisri, Dewi Yulianti; Indrayani, Ratih Rizki; Bisri, Tatang (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
Removal of spinal meningiomas in cervical 1 and 2 has several problems, especially regarding the respiratory and cardiovascular systems. A woman, 33 years old, admit Santosa Bandung Central Hospital with complaints of weakness in her left hand and both legs since 4 months ago. Weight 50 kg, height 155 cm, blood pressure 146/102 mmHg, pulse rate 105 x/min, temperature 36.50C, SpO2 98% with room air. At diagnosis of cervical myelopathy due to space occupying lesion (SOL) intradural meningioma suspect. Induction of anesthesia with fentanyl 100 mcg, propofol 60 mg, rocuronium 40 mg, ventilated with 100% oxygen and sevoflurane 3 vol% (1.5 MAC), before laryngoscopy-intubation repeated half the initial dose of propofol. The patient is intubated in an in-line position. Anesthesia maintenance with sevoflurane 1 vol%, oxygen: air 50%, dexmedetomidine continuous 0.4 mcg/kg per hour, and continuous rocuronium 10 mcg/kgBW/min. Ventilation is controlled with a tidal volume of 360 ml, frequency 14 times/min. Then the patient is positioned in the prone position. Post-surgery is admitted to the ICU and day 5 the patient can be discharged from the hospital. The effects of C12 spinal cord tumors can affect the respiratory and cardiovascular systems. Surgical trauma can aggravate the injury before recovery occurs, so it is necessary to do ventilation assistance and cardiovascular support before recovery.